Makna Simbol dan Bahasa Seni Beladiri Suliwa - Anggi Indri Yani; Fitriana Poerana, Ana; Nurkinan (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
Padepokan Suliwa Karawang was founded on 8 October 2017 by H. Karta Wiratma, Suliwa is a vital part of the local cultural heritage with a focus on martial arts. With the main aim of developing and preserving arts and culture, Suliwa is actively involved in activities such as discussions, participation in community events, and a YouTube channel. Through qualitative research using an ethnographic communication approach and the application of George Herbert Mead's Symbolic Interaction Theory and Dell Hymes' Speaking Theory to understand human communication in a social context, Suliwa succeeded in forming a unity with the participants who practice the basic principles in line with the Siliwangi Kingdom, namely "silih asah, silih asih , take care of each other." Suliwa's goal is to make Suliwa committed to developing the character of her students, creating individuals who are skilled in martial arts and have high integrity. The actions taken by Suliwa, namely by involving internal discussions, community participation, and the use of social media, not only promote but also preserve the martial art of pencak silat. The symbol and key lies in the Suliwa logo, closely related to Karawang culture, playing an important role in carrying out human obligations, especially for Muslims. The use of the pencak drum and machete as a characteristic of Suliwa's identity combines elements of music and martial arts techniques in her cultural heritage. H. Karta as the founder and professor of Suliwa always upholds communication norms and ethics, creating an environment that encourages humility and discipline according to religious teachings. Suliwa collaborates martial arts with Sundanese dance and Karawang culture accompanied by Sundanese music, Padepokan Suliwa has succeeded in creating a distinctive genre that reflects the diversity of local culture, enriches and maintains the martial arts and cultural heritage of Karawang Regency.